2017
DOI: 10.1073/pnas.1618606114
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM promotes axon fasciculation and growth in the developing optic pathway

Abstract: Although many aspects of optic pathway development are beginning to be understood, the mechanisms promoting the growth of retinal ganglion cell (RGC) axons toward visual targets remain largely unknown. Down syndrome cell adhesion molecule (Dscam) is expressed by mouse RGCs shortly after they differentiate at embryonic day 12 and is essential for multiple aspects of postnatal visual system development. Here we show that Dscam is also required during embryonic development for the fasciculation and growth of RGC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 49 publications
(55 reference statements)
5
54
0
Order By: Relevance
“…An important question is whether Dscam functions cell-autonomously to promote presynaptic growth in GABAergic neurons. Previous studies in Drosophila sensory neurons and gain-offunction studies in mouse retinal ganglion cells suggest a cell-autonomous role of Dscam in promoting axonal growth (11,22). Genetic deletion of Dscam in single ChCs is challenging because the Cre activity in Nkx2.1-CreER mouse line is weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important question is whether Dscam functions cell-autonomously to promote presynaptic growth in GABAergic neurons. Previous studies in Drosophila sensory neurons and gain-offunction studies in mouse retinal ganglion cells suggest a cell-autonomous role of Dscam in promoting axonal growth (11,22). Genetic deletion of Dscam in single ChCs is challenging because the Cre activity in Nkx2.1-CreER mouse line is weak.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, altered Dscam expression levels have been reported in multiple brain disorders, including Down syndrome (DS) (14), autism spectrum disorders (ASD) (15)(16)(17), intractable epilepsy (18), bipolar disorder (19), and possibly Fragile X syndrome (11,12,20,21). Although recent findings suggest a conserved role of Dscam in promoting presynaptic growth in vertebrates (22,23), whether dysregulated Dscam expression results in neuronal defects in brain disorders remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…EGL-44/EGL-46 targets likely include downstream effectors that mediate fasciculation of PVD 2° dendrites with motor neuron commissures. Multiple cell surface proteins including Dscam (Bruce et al, 2017), members of the L1CAM family and receptor tyrosine kinases and phosphatases (Feng et al, 2013; Van Vactor, 1998; Wu et al, 2001) as well as secreted Ig domain proteins (Aurelio et al, 2002) have been shown to mediate inter-axonal fasciculation, but much less is known of the factors that direct dendritic bundling (Barry et al, 2010). Our observation that the mec-3 PVD branching defect is more severe than that of double mutants in which both hpo-30 and egl-44 are inactivated suggests that dendrite morphogenesis also depends on other mec-3 -regulated components.…”
Section: Discussionmentioning
confidence: 99%
“…Once they pass the optic chiasm region RGC axons continue navigating to enter the optic tracts and reach the visual targets guided by other guidance molecules. The Down syndrome cell adhesion molecule ( Dscam ) seems to be important for axonal fasciculation at this level of the pathway (Bruce et al ., ). However, molecules and mechanisms guiding RGC axons once they trespass the optic chiasm, are out of the scope of this review and we will not discuss them further.…”
Section: Development Of the Optic Nervesmentioning
confidence: 97%